2014
DOI: 10.5539/ass.v10n3p186
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Knowledge and Issues in the Implementation of School-Based Assessment: A Case of Schools in Terengganu

Abstract: In tandem with educational best practices the world over, School-based assessments (SBAs) were introduced in Malaysia in 2012 for secondary one students. This study investigated quantitatively and qualitatively matters such as the teachers' knowledge of SBAs and the issues faced when implementing SBAs. Whereas the factors contributing to the problems of SBA implementation was investigated only qualitatively. A sample of 60 English teachers in the district of Dungun, Terengganu, who were involved in SBAs from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…What is worrying, previous studies conducted by (Rumahlatu et al 2016;and Samsonova et al 2020) show that teachers' readiness is at a low level when implementing changes in education. Studies by (Jamaliah, 2014;Nur Abidah, 2013;Siti Mardziah, 2013;Gopala, Roszainora, Nor Zaitolakma, Raja Nurul Huda, Azyanee, Thenmolli & Haslina, 2014) regarding teacher readiness, it was reported that teachers are not fully prepared when something changes in education implemented. The same findings were obtained by Joza Fahd (2015) and Ekwueme and Meremikwu (2013) who conducted a study on the readiness of teachers in their respective countries.…”
Section: Research Backgroundmentioning
confidence: 99%
“…What is worrying, previous studies conducted by (Rumahlatu et al 2016;and Samsonova et al 2020) show that teachers' readiness is at a low level when implementing changes in education. Studies by (Jamaliah, 2014;Nur Abidah, 2013;Siti Mardziah, 2013;Gopala, Roszainora, Nor Zaitolakma, Raja Nurul Huda, Azyanee, Thenmolli & Haslina, 2014) regarding teacher readiness, it was reported that teachers are not fully prepared when something changes in education implemented. The same findings were obtained by Joza Fahd (2015) and Ekwueme and Meremikwu (2013) who conducted a study on the readiness of teachers in their respective countries.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Teachers' readiness is defined as the ability and skills of teachers to be willing to implement teaching in the classroom (Inan & Lowther, 2010). Past studies on teachers' readiness have been conducted in Malaysia proving that teachers are not fully prepared when a change in education is implemented in the country (Jamaliah, 2014;Gopala et al, 2014;Nur-Abidah, 2013;Siti-Mardziah, 2013& Abu-Obaideh, 2012. There are similarities in the findings of studies conducted abroad by Joza (2015) in Saudi Arabia and Ekwueme and Meremikwu (2013) in Nigeria also show that teachers are not fully prepared when there is a change in education in the country.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The teachers highlighted that there was insufficient time for training, not enough opportunities to conduct practical training, and that the trainers themselves were not adequately versed in school-based assessment practices. Another study by Nair et al (2014) indicated a need for teamwork and collaboration among teachers to be improved as they faced a number of issues such as time constraints, lack of effective materials and methodologies and facilities.…”
mentioning
confidence: 99%